Schedule of Classes, Fall 2010 - University of Wisconsin-Milwaukee. Department of Enrollment Services (My University, 2010)
PDF version of the UW-Milwaukee Schedule of Classes for the Fall 2010 term. Includes registration policies and lists of available classes during this term.
Keywords: Curriculum; Academics; Department of Enrollment Services